Targeting DDX3 in Medulloblastoma Using the Small Molecule Inhibitor RK-33 - Saritha Tantravedi (Translational Oncology, 2019)
Medulloblastoma is the most common malignant tumor that arises from the cerebellum of the central nervous system. Clinically, medulloblastomas are treated by surgery, radiation, and chemotherapy, all of which result in toxicity and morbidity. Recent reports have identified that DDX3, a member of the RNA helicase family, is mutated in medulloblastoma. In this study, we demonstrate the role of DDX3 in driving medulloblastoma. With the use of a small molecule inhibitor of DDX3, RK-33, we could inhibit growth and promote cell death in two medulloblastoma cell lines, DAOY and UW228, with IC50 values of 2.5 μM and 3.5 μM, respectively. Treatment of DAOY and UW228 cells with RK-33 caused a G1 arrest, resulted in reduced TCF reporter activity, and reduced mRNA expression levels of downstream target genes of the WNT pathway, such as Axin2, CCND1, MYC, and Survivin. In addition, treatment of DAOY and UW228 cells with a combination of RK-33 and radiation exhibited a synergistic effect. Importantly, the combination of RK-33 and 5 Gy radiation caused tumor regression in a mouse xenograft model of medulloblastoma. Using immunohistochemistry, we observed DDX3 expression in both pediatric (55%) and adult (66%) medulloblastoma patients. Based on these results, we conclude that RK-33 is a promising radiosensitizing agent that inhibits DDX3 activity and down-regulates WNT/β-catenin signaling and could be used as a frontline therapeutic strategy for DDX3-expressing medulloblastomas in combination with radiation.